Hubungan Pengetahuan Tentang Dismenorhea Dengan Sikap Penanganan Pada Remaja Putri Di Sma Lab School Untad Palu - Angraeny, Ni Luh Ayu; Diana, Nita (Akademi Kebidanan Palu Sulawesi Tengah, 2019)
A pelvic area due to menstruation and production of protaglsndins. Often begins afterxperiencing the first menstruation. Dismenorha is a symptom that most often causes womento go to a doctor for consultasion and treatment. The purpose of this study is to determinethe relationship of knowledge about Dismenorhea with the attitude of handling in youngwomen in UntadPalu High School Lab. This research. The population in this study were girlsfrom UntadPalu High School Lab class X and XI with a total 0f 116 people. The number ofsampls 54 people obtained through random sampling techniques. This research datacollection in the from of primary data (Questionnarie) and secondary data. Data analysis wascarried out by means of univariate analysis and bivariate analaysis. The results of the studystated that as many as 39 people (72,2%) teenagagirs at Untad Hummer Lab School hadgood knowledge about Dismenorhea and 14 people (27,8%) had poor knowlwdgw.Furthermore, the attitude of UntadPalu Senior High School Lab School students as many as38 people (70,4%) had good attituds about Dismenorhea and 16 people (29,6) had poorattituds. Based on the rsults of bivariate nalysis using the Chi Square test showd that pvalue <0,05 then Ho was accepted Ha was rejected so it can be concluded that there is arelationship between knowlwdge about adolescent Dismenorhea with the attitude of handlingadolescent girls in High School Lab UntadPalu.